Association between fear of falling and falls following acute and chronic stroke: a systematic review with meta-analysis - Tamis W. Pin; Stanley J. Winser; Wayne L.S. Chan; Bolton Chau; Shamay Ng; Thomson Wong; Margaret Mak; Marco Pang (Medical Journals Sweden, 2024)
Objectives: To examine the association between falls and fear of falling in people with stroke and to evaluate the differences between patients with acute stroke and those with chronic stroke with regard to any such association. Methods: Articles were searched in Medline, CINAHL, AMED, Embase, PsycINFO, Cochrane Library of Reviews and PEDro from inception until March 2023. Experimental, observational or explorative studies investigating the association between fear of falling and falls in people with stroke were included. Articles were screened by 2 independent reviewers. Data were extracted by an independent reviewer. Results: A total of 26 reports were included in this review (n = 2863). Fear of falling, assessed by a single-question survey, was significantly associated with falls (relative risk = 1.44; 95% confidence interval (95% CI) = 1.22, 1.70; I2 = 0%) in people with acute stroke. Significant mean differences in fear of falling, based on the Falls Efficacy Scale (mean difference = 12.80; 95% CI = 1.81, 23.78; I² = 28%) and Activities-specific Balance Confidence Scale (mean difference = -9.99; 95% CI = -15.36, -4.62; I² = 57%), were also reported between fallers and non-fallers in people with chronic stroke. Conclusion: A small, but significant, association exists between falls and fear of falling in both acute and chronic stroke patients.